Control strategy for the combined operation of grid-connected inverter and charger - Quang-Tho Tran; Quang-Sang Le (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
Solar power sources and electric vehicles (EVs) are increasingly used because of their environmental friendliness and sustainability. They are typically connected to the power grid through devices such as inverters and chargers to either generate or receive electrical energy. These devices contain a DC voltage bus. Therefore, the combined control of these two types of devices can improve their overall operational efficiency. This article proposes a grid-connected converter with an integrated battery-charging function. In addition, it presents a control strategy for the coordinated operation of this converter during both charging and power generation at the DC bus. In this algorithm, the battery is treated as a priority load, which allows the system to eliminate the AC-DC converter used in conventional chargers. A total peak power of 9 kWp is used to investigate the processes of power generation and battery charging. The total harmonic distortions of grid current are less than 2.86% in different operational cases and meet the grid codes. The obtained results are analyzed under varying irradiance conditions to verify the effectiveness of the proposed control method.